2-Hydroxyeupatolide attenuates inflammatory responses via the inhibiting of NF-κB signaling pathways. Issue 60 (1st August 2017) - Ke, Zunli; Li, Mingxia; Liu, Xin; Tan, Si; Zhou, Zhiqin; Huang, Cheng
Abstract : 2-Hydroxyeupatolide (2-HE), a sesquiterpene lactone, is a potential agent to improve LPS-induced acute mouse inflammation damage. Abstract : 2-Hydroxyeupatolide (2-HE), a sesquiterpene lactone, was found in the genus Eupatorium that has been used for a long time in traditional Chinese medicine for the treatment of several diseases. In this study, the anti-inflammatory activity of 2-HE and the underlying mechanism of this action were explored. We demonstrated that 2-HE ameliorated hyperemia, edema, alveolar wall thickening, and inflammatory cell infiltration in the lung tissues, and inhibited the serum inflammatory cytokines, interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) of lipopolysaccharide (LPS) challenged ICR mice effectively. Besides, 2-HE inhibited the mRNA expression levels of IL-6 in lung, spleen, and hypothalamus in the mice. Moreover, 2-HE was found to suppress the production of nitric oxide (NO) and the mRNA and protein levels of TNF-α, IL-1β, and IL-6 in LPS-treated RAW 264.7 macrophage cells in a concentration-dependent manner. The mechanistic study showed that 2-HE inhibited the nuclear factor-kappa B (NF-κB) transactivity and nucleic translocation of NF-κB p65 and p-NF-κB p65 in RAW 264.7 cells. Taken together, our study suggested that 2-HE may suppress the inflammatory response through inhibiting the activation of NF-κB signaling pathways, and make a contribution to further understanding the pharmaceutical activity of Eupatorium plants.